2018
DOI: 10.1080/17470218.2017.1313873
|View full text |Cite
|
Sign up to set email alerts
|

Repetition inhibition and facilitation effects for visual-verbal stimuli under conditions of concurrent articulation

Abstract: This study examines the effects of within-sequence repetitions for visually presented consonants under conditions of quiet and concurrent articulation (CA). In an immediate serial recall (ISR) procedure, participants wrote down the six consonants in the order of original presentation. CA reduced serial recall and abolished the phonological similarity effect. However, the effects of within-trial repetitions were broadly similar under quiet and CA. Specifically, adjacent repetitions facilitated recall of the rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Specifically, using a tactile ISR task, we have demonstrated recall inhibition for a repeated item when that item is separated by two intervening items (the Ranschburg effect). This finding is consistent with a number of studies showing the effect for recall of verbal sequences (e.g., Crowder, 1968; Duncan & Lewandowsky, 2005; Henson, 1998a; Jahnke, 1969; Johnson et al, 2018; Maylor & Henson, 2000). Second, we have reported a Ranschburg effect of equivalent magnitude under conditions of both quiet and CA.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Specifically, using a tactile ISR task, we have demonstrated recall inhibition for a repeated item when that item is separated by two intervening items (the Ranschburg effect). This finding is consistent with a number of studies showing the effect for recall of verbal sequences (e.g., Crowder, 1968; Duncan & Lewandowsky, 2005; Henson, 1998a; Jahnke, 1969; Johnson et al, 2018; Maylor & Henson, 2000). Second, we have reported a Ranschburg effect of equivalent magnitude under conditions of both quiet and CA.…”
Section: Discussionsupporting
confidence: 92%
“…Under the CA condition, the phonological similarity effect (PSE) was abolished—a finding taken to reflect disruption to the process of phonological recoding of the visually presented consonant sequences (e.g., Baddeley, Lewis, & Vallar, 1984). Importantly, despite the purportedly degraded phonological representations of the consonant sequences, Johnson et al (2018) demonstrated a Ranschburg effect of comparable magnitude under conditions of both quiet and CA.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations